Artificial Intelligence as a Strategic Enabler in Human Resource Management: Transforming Information Technology Industry in Saudi Arabia - Albar, Amnah (Digital Repository of Theses, 2026)
This study examines the adoption and integration of Artificial Intelligence (AI) in Strategic Human Resource Management (SHRM) within organisations in Saudi Arabia. The research investigates the key factors influencing AI implementation in HR functions, the major challenges organisations encounter, the strategic opportunities AI creates for enhancing HR effectiveness and workforce development, and the recommendations necessary for successful integration. Using a quantitative research design, data were collected through a structured questionnaire administered to IT professionals within IT industry. Sample size of the study was 600 information technology professionals working in Saudi Arabia cities namely, Riyadh, Jeddah, and Dammam. Statistical analyses, including reliability testing, descriptive statistics, correlation, and regression analysis, EFA were conducted to evaluate the relationships between AI adoption and organisational performance outcomes. The findings indicate that technological readiness, leadership support, organisational culture, and digital competencies significantly influence AI adoption in HRM. While AI offers strategic benefits such as improved talent acquisition, predictive workforce analytics, enhanced employee engagement, and data-driven decision-making, organisations face challenges including resistance to change, limited technical expertise, high implementation costs, and ethical concerns related to data privacy and algorithmic bias. The study further reveals that effective governance frameworks, employee upskilling, and strategic alignment are critical for maximizing AI-driven HR performance. Overall, the research contributes to the growing body of knowledge on AI-enabled SHRM in emerging economies and provides practical recommendations for organisations and policymakers to foster sustainable digital transformation aligned with Saudi Arabia’s Vision 2030 objectives. Keywords: artificial intelligence (AI), competitive advantage, organisational performance, strategic human resource management (SHRM), technologies